Seeing Optimism in times of COVID-19: An initial study on the significant predictors of optimism among emerging adults in times of pandemic crisis - Dela Cruz, Nolein Verniz V.; Parcon, Apryl Mae C. (Diliman Review, 2024)
This study aimed to know the factors that predicts optimism among those in the stage of emerging adulthood, a stage where a lot of transitions are happening, during a time of pandemic where a lot of uncertainties are experienced.  The dimensions of emerging adulthood (Reifman, 2007) and protective factors (Ponce-Garcia, et. al., 2015) were posited as possible predictors of optimism.  A total of one hundred ninety-nine Filipino young adults ( n=199) participated in the study. Among the dimensions of emerging adulthood, experimentation, self-focus, and other-focus positively correlated with optimism, while negativity and feeling-in-between negatively correlated with optimism. Among the protective factors, social support, social skill, planning behavior and goal efficacy positively correlated with optimism. Taking all these factors together, regression analysis showed that having social support and goal-efficacy best predicts optimism among young adults. The implications of this were further discussed in line with the present situation of Covid-19 pandemic crisis.